O PRINCÍPIO DA GRATUIDADE ATIVA NO PROGRAMA DE ASSISTÊNCIA ESTUDANTIL DO INSTITUTO FEDERAL DE EDUCAÇÃO, CIÊNCIA E TECNOLOGIA DE SÃO PAULO (IFSP) – CAMPUS CUBATÃO - MENDONÇA, GISELA DE BARROS ALVES (2015)
This work, initially based on the analysis of some documents related to the current Brazilian educational legislation aims to develop an investigation about the applicability of the student assistance within the Federal Institute of Education, Science and Technology of São Paulo (IFSP). Based on the right to education of every citizen, which our Constitution guarantees, the Government created in 2010, the National Student Assistance Program (PNAES). Supported by this Program, the IFSP created in 2011, the Student Assistance Program (SAP), giving validity and continuity to the actions developed in Campi to minimize evasion and school failure, in order to ensure the permanence of the students in that Institute. Although SAP has been implemented in all Campi of IFSP, this work aims to analyze and study specifically the Campus Cubatão, located in the Santos region because, among others, this has been the first decentralized unit of the Federal Institutes of the country. In this study, our goal is to analyze the operating structure of the IFSP with the specific intention of investigating the Campus of Cubatão. Also checking the Social Vulnerability issues found in this renowned institution and investigating the actions of PAE born of PNAES, observing the applicability of this program based on the principle of Active Gratuity and the right to education of every citizen. Therefore, we use fundamentally, not only the aforementioned legislation, but also the principle Melchior´s Active Gratuity (2011) and the concept of social vulnerability proposed by Alves (1994) and Abramovay (2002).